Smart Village Accountability: Comparative Study in Management BUMDes Tirta Mandiri and BUMDes Giritama As a Village Income Earner in 2018 - Muhammad Dwi Nurfaisal; Dyah Mutiarin; Herdin Arie Saputra; Ikhwan Rahmatika Latif (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2020)
This study aims to determine how smart village accountability in the comparative study of BUMDes management as income generating in Ponggok Village, Polanharjo District, Klaten Regency and Dlingo Village, Dlingo District, Bantul Regency. The implementation of smart villages in Indonesia is a representative form as a fulfillment of the needs so that villages are able to overcome the problems that occur in it (Sensing), understand and understand the problems that occur (understanding), and are able to regulate (Controlling) the resources they have so that they can be used effective and efficient way to improve the quality of life of rural communities. In its implementation between BUMDes Tirta Mandiri and BUMDes Giritama which have several management differences in an effort to improve the welfare of the community. The type of research used is a qualitative approach. Data collection methods use in-depth interview techniques (In-Dept Interview). Analyzes were performed using the Nvivo 12 Plus software.